Effectiveness of non-pharmacological interventions in managing dyspnea among cancer patients: A systematic review - Feri Atmajaya; Allenidekania Allenidekania; Yati Afiyanti; Dewi Gayatri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The management of dyspnea in cancer patients still faces various challenges. Non-pharmacological interventions are increasingly recognized as effective, potentially cost-effective, and effective approaches to managing this symptom. Purpose: To identify, evaluate, and analyze evidence regarding the effectiveness of non-pharmacological interventions in managing dyspnea in cancer patients. Method: This systematic review followed PRISMA guidelines and conducted a literature search across five databases (Sage Journals, PubMed, ScienceDirect, Springerlink, and Google Scholar). Inclusion criteria included English-language articles published between 2015 and 2025, with a randomized controlled trial (RCT) or cohort study design. From 59,225 articles identified, 11 studies met the inclusion criteria for analysis. Results: A total of 1,369 cancer patients were analyzed across 10 RCTs and one cohort study. Various non-pharmacological interventions proven effective in managing dyspnea include Tai Chi, aerobic exercise, Respiratory Distress Symptom Intervention (RDSI), Inspiratory Muscle Training (IMT), home-based education programs, and acupuncture. Conclusion: Non-pharmacological interventions can be an important component in the management of dyspnea in cancer patients, significantly contributing to symptom reduction and overall patient well-being.